For sustainable educational design for all - Mirca Montanari (International Journal of Educational Innovation and Research, 2023)
This contribution intends to propose some reflections on sustainable and accessible educational design, starting from the analysis of today’s educational contexts called upon to promote processes of pedagogical revisitation on the wave of both the profound discomforts and the unprecedented opportunities offered by the pandemic. In the name of the generative gaze that should accompany every process of change between past and future, between awareness achieved and the search for new territories to be explored, the school narrative of a pupil with special needs is proposed, aimed at enhancing the inclusive design interventions concerted and synergic between secondary school, family and out-of-school.